Concentration and Release of Phosphorus and Potassium From Lignocellulosic- and Manure-Based Biochars for Fertilizer Reuse - Novak, Jeffrey M.; Johnson, Mark G.; Spokas, Kurt A. (Frontiers in Sustainable Food Systems, 2018)
Biochars pyrolyzed from plant residues and animal manure feedstocks may contain disproportionate amounts of phosphorus (P) and potassium (K). Unequal nutrient characteristics can impact the biochars ability to properly supply as well as improve soil P and K fertility levels. A soil incubation study was performed to test the hypotheses that biochar produced from poultry litter will release more water soluble dissolved P (DP) and K (DK) concentrations and would also increase soil plant available P and K concentrations as compared to lignocellulosic-based biochars. Biochar was pyrolyzed at 500°C from hardwood waste products (HW), pine chips (PC; Pinus taeda), poultry litter (PL; Gallus domestics), and an 80:20 pine chip/poultry litter blend, which were then added at 20 g kg−1 to a sandy Norfolk E soil (Typic Kandiudult). Un-amended (no biochar) Norfolk E soil served as a control. During the incubation, all treatments were leached four times with deionized water and the leachate analyzed for DP and DK; their concentration and mass released as a function of total amounts present were then calculated. At the conclusion of the study, soils were extracted using Mehlich-1 reagent for determination of plant-available P and K contents. Leachates from soil amended with 100% PL biochar and the 80:20 blend had significantly more DP and DK mass (59 and 1,018 mg, respectively) released compared to PC and hardwood biochars (0.07 and 23 mg). Significant amounts of DP were released from PL biochar with additional water leaching, but DK release results were mixed. Soil Mehlich-1 P and K contents were significantly increased using PL biochar compared to lignocellulosic-based biochars. Blending PC with PL feedstocks at 80:20 weight ratio reduced Mehlich-1 soil P concentrations to 35 mg kg−1, which was more aligned with soil test P levels (30–50 mg kg−1) recommended for a corn (Zea mays) production in southeastern USA Coastal Plain sandy soils. These results reveal that 100% PL biochar offers a higher potential to provide more P and K to soils than lignocellulosic based biochars, and that feedstock blends can be used to create designer biochars that align soil test fertilizer values with plant nutrient requirements.